Cycling as a Part of Daily Life: A Review of Health Perspectives. Issue 1 (2nd January 2016) - Götschi, Thomas; Garrard, Jan; Giles-Corti, Billie
Abstract: Health aspects of day-to-day cycling have gained attention from the health sector aiming to increase levels of physical activity, and from the transport and planning sector, to justify investments in cycling. We review and discuss the main pathways between cycling and health under two perspectives — generalizable epidemiological evidence for health effects and specific impact modeling to quantify health impacts in concrete settings. Substantial benefits from physical activity dominate the public health impacts of cycling. Epidemiological evidence is strong and impact modeling is well advanced. Injuries amount to a smaller impact on the population level, but affect crash victims disproportionately and perceived risks deter potential cyclists. Basic data on crash risks are available, but evidence on determinants of risks is limited and impact models are highly dependent on local factors. Risks from air pollution can be assumed to be small, with limited evidence for cycling-specific mechanisms. Based on a large body of evidence, planners, health professionals, and decision-makers can rest assured that benefits from cycling-related physical activity are worth pursuing. Safety improvements should be part of the efforts to promote cycling, both to minimize negative impacts and to lower barriers to cycling for potential riders.